A Secure Key Exchange Protocol and a Public Key Cryptosystem for Healthcare Systems (Contemporary Mathematics, 2024)
Diffie-Hellman (DH) is the reason for the existence of a solution to the key distribution problem, where two parties can mutually set up a shared secret key over an insecure channel without any previous communication. In this study, a novel key exchange protocol based on the difficulty of the Discrete Logarithm Problem with Factor Problem (DLPFP) utilizing matrices in non-commutative semigroup over semiring is proposed. The security and complexity analyses of the protocol are discussed. Also, an ElGamal cryptosystem based on a group of invertible matrices and DLPFP over a semiring to encrypt the Sensitive Health Information (SHI) in healthcare systems is suggested.
Keywords: public key cryptography, key exchange protocol, Diffie-Hellman, ElGamal cryptosystem, semiring